Main Features of IV + V Software Package and the Scope of its Application in Indian Context - Satyanarayana, R. (Journal of Information and Knowledge, 1987)
Describes the main features of IV + V software package. Explains the principles underlying its design and architecture. Discusses development of applications using the package. Opines that IV + V package could prove very useful in our present day context, especially when the Indian computing industry is manufacturing micro-computer systems on which this package could be installed and used for developing Information Storage and Retrieval Systems and for automating library operations.